Measuring readiness for entrepreneurship: An information tool proposal - Alicia Coduras; José Manuel Saiz-Alvarez; Jesús Ruiz (Journal of Innovation & Knowledge (JIK), 2016)
A profound review of the literature on entrepreneurship reveals that it does not exist a specific information tool to measure the individuals' readiness for entrepreneurship. The purpose of this research has been building such kind of instrument to estimate the individuals' readiness for entrepreneurship. Its design takes in consideration the inclusion of the main variables identified by the literature as those most associated with entrepreneurial profiles. These variables have been grouped into three categories: sociological, psychological and managerial-entrepreneurial. Each group provides batteries of items which are evaluated thanks to a specific scoring system. The final objective is to provide a system to calculate individual scores of readiness for entrepreneurship and, at the same time, partial scores on concrete aspects of it. The information tool is presented at this paper and will be tested and refined in the near future.
Keywords: M; M1; M2; M5; M13; C91; 650; Readiness for entrepreneurship; Information tool; Entrepreneurs' features; Measurement; Psycho-tests; Entrepreneurial capacity